PENGARUH PENGALAMAN AUDITOR, KOMPETENSI PROFESIONAL, DAN KOMPLEKSITAS TUGAS TERHADAP AUDIT JUDGMENT (STUDI PADA KANTOR AKUNTAN PUBLIK DI KOTA SURABAYA) - Novia Eka Rahmadanty; Muslimin Muslimin (Behavioral Accounting Journal, 2020)
The research purpose is to determine and empirically test the effect of auditor experience, professional competence, and task complexity on audit judgment. The research using quantitative approach. The research is using population sample of the auditor who works under the Public Accountant Office (KAP) in the Surabaya, which is registered in the IAPI 2019 Directory. Sampling in this research uses probability sampling techniques with a simple random sampling method and a sample of 52 auditors is obtained. The analytical method used is multiple linear regression using data quality tests, normality tests, classic assumption test, and hypothesis testing using SPSS version 23. The results of this study indicate that the auditor's experience, professional competence, and task complexity simultaneously influence on audit judgment. Partially, auditor experience and professional competence has negative and not significantly effect on “audit judgment”. While the “task complexity has a positive and significant effect on audit judgment.